The Destruction of the City: Loss in the Greek and Roman Memory - Jancsovics, Fanni (Acta Classica Universitatis Scientiarum Debreceniensis, 2022)
The appearance of the ethnically “Other” naturally has an impact on a society’s own identity. It provokes the confirmation or rephrasing of identity. The loss and destruction caused by an ethnically “Other” group creates an especially deep conflict in the society’s self-definition. This paper focuses on such events and the collective memory concerning these, through the case study of the Persian sack in 490 BC and one hundred years later the Gallic siege of Rome.